Future campus : design quality in university buildings - Taylor, Ian, (Architect); RIBA Enterprises; Higher Education Design Quality Forum (Newcastle upon Tyne, England : RIBA Publishing, 2016)
"Produced in association with the Higher Education Design Quality Forum (HEDQF), this book aims to help architects, design teams and university clients in their pursuit of practical and innovative solutions for the creation of higher education learning environments. This book argues that investment in the higher education sector is a driver for intellectual, social and economic development, offering opportunities for positive impacts for the physical environment on the character and performance of higher education. Good outcomes result from good design, which should address elements such as learning from best current practice, the importance of clear briefing, good environmental performance, positive social impacts and, also, the importance of ensuring a beautiful outcome. Including abundant examples of solutions to design problems and advice on best practice, it has contributions from leading-edge practices and academics, including case studies with highly illustrated project examples. All this is underpinned by an understanding of the practicalities of working in the sector as well as the socio-political and economic contexts and the trends shaping future practice."--Publisher's description.
"Produced in association with the Higher Education Design Quality Forum (HEDQF)"--Page 4 of cover.
Includes bibliographical references (pages 168-173) and index
ARC
Keywords: College buildings -- Aesthetics; Universities and colleges -- Designs and plans; Universities and colleges -- Planning; Architecture; College buildings